Molecular biomarkers: a US FDA effort. (April 2010) - Hong, Huixiao; Goodsaid, Federico; Shi, Leming; Tong, Weida
Molecular biomarkers are used for various purposes, including disease diagnosis and prognosis, prediction and assessment of treatment response, and safety assessment. There has been a significant increase in the number of US FDA-approved drug labels containing information on molecular biomarkers over the last decade. Almost every pharmaceutical company has been developing molecular biomarker programs, either alone, through partnerships or other ventures. More molecular biomarkers are expected to be identified and validated in drug development, and used to support approval of drug products. This article summarizes the current status of molecular biomarkers used for FDA-approved drug products, and discusses the challenges and future perspectives for the identification and qualification of molecular biomarkers. Specific FDA programs and research projects related to molecular biomarkers are also discussed for supporting regulatory review in the future.